Ramos, Gabriela. Death and Conversion in the Andes: Lima and Cuzco, 1532-1670. Notre Dame, IN: University of Notre Dame Press, 2010, 368 pp., mapas, ilustr. - Penry, Elizabeth (2011)
No presenta resumen